Review : Identifikasi senyawa bioaktif utama dalam daun leilem (Clerodendrum minahassae) dan potensi farmakologis - Sambou , Christel (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2024)
Clerodendrum minahassae leaves contain various bioactive compounds, including flavonoids, alkaloids, saponins, and phenolic acids, contributing to their pharmacological activity. This study aims to identify the main bioactive compounds in Leilem leaves (Clerodendrum minahassae) and their pharmacological potential through a literature review of various relevant scientific sources. The methodology employed includes systematic observation and meta-analysis. This review article describes the compounds present in Leilem leaves and evaluates their pharmacological activities, thereby enhancing the understanding of this underexplored medicinal plant. The findings indicate that Leilem leaves hold substantial potential as a source of bioactive molecules with diverse pharmacological properties. Based on a review of multiple scientific research articles, it can be concluded that Leilem leaves exhibit considerable efficacy in antimicrobial, anti-inflammatory, and antioxidant activities, as well as in reducing blood glucose levels.